The influence of shooting practice methods with beef and game concepts on the basketball shooting results of junior high school students - Rian Satria Almi; Asep Sujana Wahyuri; Phil Yanuar Kiram; Hendri Neldi (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to determine the effect of shooting practice methods with beef and game concepts on the basketball shooting results of extracurricular students of Islamic State Junior High School Rambah Technology. The research population of all students who participated in extracurricular SMP Islam Teknologi Rambah amounted to 40 people. The sample amounted to 40 people with a sampling technique, namely total sampling. The method used in this study is experimental (pretest postest design). The instrument used is a test to measure basketball shooting results. Data analysis techniques use normality tests and homogeneity tests. The results of this study are 1) There is a significant influence of the BEEF concept exercise on the basketball shooting results of extracurricular students of the Islamic State Junior High School Rambah Technology. 2) There is a significant influence of Game concept training on the basketball shooting results of extracurricular students of Islamic State Junior High School Rambah Technology. 3) There is a significant difference in the effect between BEEF and Game training on the basketball shooting results of extracurricular students of Islamic State Junior High School Rambah Technology. From the calculations that have been done, a t value of 0.892 was obtained, and it turned out to be smaller ttable 5%, which is 2.10. The BEEF concept exercise has a better effect on the basketball shooting results of extracurricular students of the Islamic State Junior High School of Rambah Technology. The increase in the ability of group 1 BEEF concept training was 51.1% and group 2 (the group that received the Game concept training treatment) was 36.1%. It was concluded that the BEEF concept exercise had a significant influence on improving the basketball shooting ability of extracurricular students of the Islamic State Junior High School of Rambah Technology compared to the Game concept exercise.